القياس في مسائل العقيدة: دراسة تأصيلية - العميري، سلطان بن عبدالرحمن بن حميد (جامعة الأميرة نورة بنت عبد الرحمن, 2020)
The research idea centers round a central question, its result is: finding out whether or not analogy can be used as evidence for theological (aqeedah) matters. The answer to this matter is only reached through detailing and differences, as theological matters are different kinds, and analogy is also different kinds, so you would have to identify the kind of theological issue and its nature in accepting the different kinds of analogy or not. The research compass focuses - based on this variety -on solving three main questions: The first question: defining qiyas al-tard, and explaining the nature of the theological issues that accept qiyas al-tard and those that don’t, and listing the effective limits in this issue, and mentioning a few applications to illustrate this issue. The second question: defining qiyas al-aks, and explaining its application in theological matters and its effect in building opinions. The third question: revoking contradicting positions in making analogy work for theological matters, and stating the influencing factors in these positions, and listing the categories of opposers, and uncovering the origins of mistakes with each group. Thus this research combines between thoroughness and rooting in this subject and between criticism and revoking certain opinions that contradict the correct position and the straight path in making analogy work for theological matters.
تتمحور فكرة البحث في قضية مركزة، حاصلها: تحديد ما إذا كانت مسائل العقيدة يصح أن يستدل فيها بالقياس أم لا. وتحرير الرؤية في هذه القضية لا يتحقق إلا بالتفصيل والتفريق، فمسائل العقيدة أنواع، والقياس أنواع، فلا بد إذن من تحديد كل نوع من المسائل العقدية، وتحديد طبيعته في قبول أنواع القياس المختلفة أو عدمه. وانحصرت بوصلة البحث بناء على هذا التنوع في معالجة ثلاث قضايا أساسية: القضية الأول: تعريف قياس الطرد، وبيان طبيعة المسائل العقدية التي تقبل قياس الطرد والتي لا تقبله، وتحديد الضوابط المؤثرة في هذه القضية، وذكر عدد من التطبيقات الموضحة للموضوع. القضية الثانية: تعريف قياس العكس، وبيان تطبيقاته في مسائل العقيدة وأثره في بناء المواقف والآراء حولها. القضية الثالثة: نقض المواقف المخالفة في إعمال القياس في مسائل العقيدة وبيان المنطلقات المؤثرة في تلك المواقف، وتحديد أصناف المخالفين فيها، والكشف عن أصول الغلط عند كل صنف منهم. فالبحث يجمع بين التأصيل والتقعيد في هذا الموضوع وبين النقد والإبطال للمواقف المخالفة للتأصيل الصحيح والمسلك المستقيم في قضية إعمال القياس في مسائل العقيدة.
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- العقيدة الإسلامية -- الدراسات التأصيلية